PENDAMPINGAN BADAN USAHA MILIK DESA (BUMDES) DALAM OPTIMALISASI POTENSI DESA DI DESA CEPAKA TABANAN-BALI - I Nengah Aristana; I Made Yudi Darmita; I Putu Bagus Suthanaya; Putu Agus Prayogi (Universitas Triatma Mulya, 2021)
Community service that is carried out has a purpose, namely it is expected to be able to provide benefits in the form of increasing entrepreneurial practices, related; maximizing potential, management capabilities, understanding business plans and their implementation, as well as increasing the ability to collaborate with external parties. In addition, it can improve business management that has been running and improve the quality of records owned. The methods used are 1) the presentation method is used to deliver detailed material and examples related to entrepreneurship, 2) the discussion method, 3) the simulation method and operational assistance. The activity was attended by the Cepaka Village BUMDes management/manager. Based on the assistance provided and observations, it can be seen that the participants followed and responded positively to each given program. Furthermore, they feel this assistance is very useful to assist them in carrying out their business operations.